No Differential Reward Responsivity and Drive, Punishment Sensitivity or Attention for Cues Signaling Reward or Punishment in Adolescents With Obesity - Jonker, Nienke C.; van Malderen, Eva; Glashouwer, Klaske A.; Vervoort, Leentje; Braet, Caroline; Goossens, Lien; de Jong, Peter J. (Frontiers in Psychology, 2019)
Although it has been proposed that obese and healthy weight individuals might differ in their reward and punishment sensitivity, the literature shows diverse and inconsistent findings. The current study was set out to examine the role of reward and punishment sensitivity in adolescent obesity by differentiating between reward responsivity and reward drive, and by complementing self-report measures with performance-based measures indexing attention for cues signaling reward and punishment as well as effort to approach reward and avoid punishment. Participants were adolescents aged 12-23, with obesity (n = 51, adjusted BMI between 143 – 313), and with a healthy weight (n = 51, adjusted BMI between 75 – 129). Individuals with obesity reported lower reward responsivity than adolescents with a healthy weight, whilst there were no differences in reward drive or attention to cues signaling reward. These findings seem in line with the reward deficiency theory that posits that obese and severe obese individuals might be characterized by lowered sensitivity to reward, for which they try to compensate by eating highly palatable foods. No differences in self-reported punishment sensitivity or attention for cues signaling punishment were found between obese and healthy weight adolescents.